(untitled) (Update Dental College Journal, 2019)
Background: Acetylsalicylic acid (ASA) generically known as Aspirin is an analgesic, antipyretic, anti-inflammatory and also an antiplatelet drug. In order to avoid excessive bleeding and to be on the safer side, dentists have traditionally advised their patients to stop taking aspirin before extraction of teeth although this surgical procedure can be done without cessation of aspirin intake. Objective: The purpose of the study was to assess the necessity of interrupting aspirin therapy prior to dental extraction. Materials and Methods: A cross sectional study was conducted in November 2015 at outpatient department of dentistry, BIRDEM Hospital, Dhaka. Sample of 50 patients who took low dose aspirin (75mg) once daily were purposely selected for this study. The blood pressure of all the subjects was recorded preoperatively. The extractions were done atraumatically under local anesthesia using 2% lidocaine with 1:100,000 epinephrine. A gelatin sponge piece was placed in socket and closed by atraumatic silk. The subjects were instructed to apply pressure pack with sterile gauze for 30 min. Evaluation was done in every 10 minutes for 30 minutes. Results: Among 50 patients, 82.0% patients were suffering from IHD. Simple extraction was done in 92.0% of patients while the remaining extractions were done surgically. 68% was managed by pressure pack and gelatin sponge while 26.0% were managed by pressure pack only. According to Post-extraction bleeding, it was found that the bleeding time was 10 min in case of 94% patients while only 2% showed 30 minutes of bleeding time. Conclusion: The study revealed that it is not necessary to alter or stop aspirin therapy and local hemostatic measures are sufficient to control bleeding. Therefore it can be assumed that extraction can be done without cessation of low dose aspirin and avoiding the life threatening issues. Update Dent. Coll. j: 2019; 9 (1): 32-36